2003
DOI: 10.1017/s2071832200012013
|View full text |Cite
|
Sign up to set email alerts
|

An Economic Analysis of Consumer Protection in Contract Law

Abstract: The traditional justification of consumer protection is founded on the notion of restraining the monopoly power of huge companies and the potential that they posses to influence consumers via advertising that limits consumers’ ability to verify what is in their own best interest. This theory refers not to the individual consumer in a concrete situation, but stresses a general economically weaker position of the consumer vis-à-vis the suppliers. Consumers are seen as less knowledgeable and as economically infer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…The 'inequality of negotiating power' theory emphasises the consumer's economically weaker status than suppliers (Haupt, 2003;Liyang, 2019;Porter, 1979). The 'inequality in bargaining power' principle emphasises the customer's economically inferior position to suppliers (Haupt, 2003). The 'exploitation theory' also supports a similar view to the 'weaker party' argument.…”
Section: Theoretical Frameworkmentioning
confidence: 94%
See 1 more Smart Citation
“…The 'inequality of negotiating power' theory emphasises the consumer's economically weaker status than suppliers (Haupt, 2003;Liyang, 2019;Porter, 1979). The 'inequality in bargaining power' principle emphasises the customer's economically inferior position to suppliers (Haupt, 2003). The 'exploitation theory' also supports a similar view to the 'weaker party' argument.…”
Section: Theoretical Frameworkmentioning
confidence: 94%
“…Therefore, due to low bargaining power, it is agreed that their interests need to be secured. The 'inequality of negotiating power' theory emphasises the consumer's economically weaker status than suppliers (Haupt, 2003;Liyang, 2019;Porter, 1979). The 'inequality in bargaining power' principle emphasises the customer's economically inferior position to suppliers (Haupt, 2003).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…For instance, Scandinavian national consumer law does not envisage an "average" consumer benchmark in the legislation, which is resulted in the formation of a type of "weak", "vulnerable" consumers and a higher standard of their protection 27 . Nevertheless, according to the Supreme Court of Finland, as a result of the full harmonization of the Unfair Commercial Practices Directive 2005/29/EC, when applicable, the traditional image of the irrational consumer goes backward and the court relies on the EU average consumer standard 28 . Meanwhile, studies in modern economics, psychology, and neuroscience have also revealed that the information paradigm is a symbol of consumer law in modern England 29 .…”
Section: Image Of the Consumer And The Information Paradigmmentioning
confidence: 99%
“…Therefore, it is accepted that their interests should be protected due to inferior bargaining power. The doctrine of 'inequality of bargaining power' stresses the economically weaker position of the consumer vis-a-vis the suppliers (Haupt, 2003). As Barnhizer (2005) points out from the United Sates case law, "gross inequality of bargaining power could negate the meaningfulness of choices available to the weaker party".…”
Section: Theoretical Frameworkmentioning
confidence: 99%